Energy IoT Architecture: From Theory to Practice - McCafferty, Stuart (Artech House Publishers, 2022)
This book provides a very common-sense approach to transforming the Electricity Industry to meet clean energy goals and simplifying coordination with DER at scale with plug and play interoperability over time. It shows you a new way to architect solutions using a modern, event-driven, standards-based, elastic, cloud-based, distributed architecture to simplify and abstract communications with utility, customer, and third-party owned clean energy assets.The book describes the architectural and technological problems of our 20th Century centralized model and provides a pragmatic alternative architecture with examples of how to seamlessly integrate large numbers of Distributed Energy Resources (DER) with centralized systems that take advantage of intelligent edge devices through coordination instead of direct command and control. It also includes references to DOE's Laminar Grid Architecture philosophy and shows how the Energy IoT Reference Architecture is aligned to solve today's biggest Electricity Industry problems.You'll find detailed explanations of common energy IoT reference architecture; understand integration of utility, customer, and third party distributed grid assets to support grid services and market opportunities, and master the elastic scalability solution which is considered by many to be the biggest problem in utility systems for DER. This is a must-have resource for architects, engineers, software developers, government officials, undergraduate students, and professors.